Reimagining English Learning with Artificial Intelligence: Boosting Engagement and Achievement in Young Learners - Agatha Kristi Pramudika Sari; Irfan Fajrul Falah Falah; Neng Lia Yulianengsih; Muhammad Fisa Al Iqbal (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2026)
Learning engagement is an essential component of effective English language instruction, as it directly influences students’ ability to achieve learning outcomes. This study aimed to investigate the impact of Artificial Intelligence (AI)-based learning on students’ engagement and learning outcomes in elementary English classes. Employing a mixed-methods approach, qualitative data were collected through observations and questionnaires, while quantitative data were obtained from pre- and post-tests. The participants consisted of 42 fourth-grade elementary school students (18 males and 24 females), divided into two groups: a control group receiving conventional instruction and an experimental group utilizing AI-based learning. The findings revealed that AI-based learning significantly enhanced students’ engagement across three dimensions—cognitive, emotional, and behavioral. Furthermore, AI integration effectively improved learning outcomes, as shown by a significant increase in post-test average scores from 72.88 to 83.29 in the control group and from 72.00 to 91.95 in the experimental group. The significance value (Sig. = 0.00 < 0.05) confirmed that the improvement was statistically significant. Therefore, the integration of AI in elementary English learning can serve as an effective alternative approach to promote greater learning engagement and enhance academic performance.